2011
DOI: 10.1007/s11414-011-9252-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving Satisfaction in Patients Receiving Mental Health Care: A Case Study

Abstract: Patient satisfaction is increasingly becoming an important component of quality for behavioral health care systems. The following report describes Group Health Cooperative's Behavioral Health Services department experiences over a 5-year period in moving from uncertainty about the value of patient satisfaction and the ability to positively impact patient ratings to achieving a significant improvement in patient ratings of satisfaction with mental health care. In this process, the Behavioral Health Department d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Slower to occur has been the evaluation of patient satisfaction in randomized controlled trials (Kelley, Kraft-Todd, Schapira, Kossowsky, & Riess, 2014), especially in the field of smoking cessation or substance abuse treatment in general (Carroll & Rounsaville, 2003). Observational studies generally support a positive relation between patient satisfaction and substance use outcomes (Boden & Moos, 2009; Carlson & Gabriel, 2001; Crosier, Scott, & Steinfeld, 2012; Hawkins, Baer, & Kivlahan, 2008; Hser, Evans, Huang, & Anglin, 2004; Sanford, Donahue, & Cosden, 2014, c.f., McLellan & Hunkeler, 1998). For example, in a large national panel survey involving patients at 62 methadone, outpatient, and residential programs in the U.S., positive treatment satisfaction near discharge predicted improved drug use outcomes at 1-year, controlling for baseline patient characteristics, treatment duration, counseling intensity, and treatment adherence (Zhang, Gerstein, & Friedmann, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slower to occur has been the evaluation of patient satisfaction in randomized controlled trials (Kelley, Kraft-Todd, Schapira, Kossowsky, & Riess, 2014), especially in the field of smoking cessation or substance abuse treatment in general (Carroll & Rounsaville, 2003). Observational studies generally support a positive relation between patient satisfaction and substance use outcomes (Boden & Moos, 2009; Carlson & Gabriel, 2001; Crosier, Scott, & Steinfeld, 2012; Hawkins, Baer, & Kivlahan, 2008; Hser, Evans, Huang, & Anglin, 2004; Sanford, Donahue, & Cosden, 2014, c.f., McLellan & Hunkeler, 1998). For example, in a large national panel survey involving patients at 62 methadone, outpatient, and residential programs in the U.S., positive treatment satisfaction near discharge predicted improved drug use outcomes at 1-year, controlling for baseline patient characteristics, treatment duration, counseling intensity, and treatment adherence (Zhang, Gerstein, & Friedmann, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Feedback from patients has also been used to inform modifications to services that then lead to improved patient satisfaction (Crosier et al, 2012), with implications for improved treatment engagement and outcomes going forward. In the smoking cessation research literature, this is particularly evident in efforts to develop and evaluate technology-based interventions, including telemedicine (Richter et al, 2015), web-based (Shahab & McEwen, 2009) and text messaging-based (Kong, Ells, Camenga, & Krishnan-Sarin, 2014) programs.…”
Section: Introductionmentioning
confidence: 99%
“…Group Health, a consumer-governed, non-profit health system in Washington state and North Idaho, has an aggressive incentive program that rewards community practitioners contracting with Group Health who score above the 90th percentile on a consolidated metric of five measures included in quarterly provider profiles (Alliance of Community Health Plans 2009). In addition, the Group Health Cooperative Behavioral Health Service Department engaged in a 5 year initiative to improve patient satisfaction; changes in the mean scores of satisfaction ratings were analyzed from 2002 to 2007 across a number of satisfaction items including access to initial appointments and coordination of care (Crosier et al 2012). However, a study on depression outcomes for primary care providers by Katon et al (2000) found no important differences in quality of care or patient outcomes, when random effects models were used to estimate mental health care provider quality.…”
Section: Introductionmentioning
confidence: 99%
“…For a number of years, Group Health had been focused on improving patient satisfaction as measured by patient response to surveys assessing satisfaction with overall treatment (Crosier et al 2012). Some initial work indicated that regular use of progress monitoring tools such as the Burns Mood Enhancement Scale (Burns 1997) and Outcome Rating Scale (Miller et al 2003), increased patient satisfaction scores.…”
Section: Getting Started/a Case For Changementioning
confidence: 99%
“…Questions related to substance use (Audit C) have become part of a department initiative to screen and conduct brief interventions for mental health patients with co-occurring substance use disorders. Clinicians have used the questions related to the therapeutic alliance as a starting point for conversations with patients about issues in the therapeutic relationship, which has been found to be related to patient satisfaction (Crosier et al 2012).…”
Section: Integration Of Mhpmt Into Clinical Processes Of Carementioning
confidence: 99%